Time for a change of practice: the real-world value of testing for neuronal autoantibodies in acute first-episode psychosis - Thomas A. Pollak; Belinda R. Lennox (BJPsych Open, 2018)
It is time that all patients with acute-onset psychosis are screened for autoimmune encephalitis, that lumbar puncture becomes a routine psychiatric investigation and that immunotherapy is available in indicated cases. We call for a culture change in the management of psychosis by psychiatry.